Speculative petroleum systems of the Punta del Este Basin (offshore Uruguay) - Morales, Ethel; Chang, Hung Kiang [UNESP]; Soto, Matias; Veroslavsky, Gerardo; Conti, Bruno; Ana, Hector de Santa; Correa, Fernando Santos [UNESP] (Soc Brasileira Geologia, 2017)
The Uruguayan continental margin was generated as the result of the breakup of Gondwana and, later, the opening of the South Atlantic Ocean, which began in the Jurassic. Three major areas of Meso-Cenozoic sedimentation are located in the Uruguayan offshore: the Punta del Este Basin, the southernmost sector of the Pelotas Basin and the Oriental del Plata Basin. These basins share the classical stages of tectono-sedimentary evolution of the other Atlantic basins, including the prerift (Paleozoic), rift (Jurassic-Early Cretaceous), transition (Barremian-Aptian) and postrift (Aptian-present) phases. Based on the analysis of basin evolution through seismic sections and well data as well as on the establishment of analogies with productive Atlantic basins, four speculative petroleum systems are proposed for the Punta del Este Basin: 1) Marine petroleum system of the prerift stage: Devonian/Permian-Devonian/Permian(?), 2) Lacustrine petroleum system of the synrift stage: Neocomian-Neocomian(?), 3) Marine petroleum system of the Cretaceous postrift: Aptian-Late Cretaceous(?), 4) Marine petroleum system of the Cenozoic postrift: Paleocene-Paleogene/Neogene(?).
Keywords: petroleum system; tectono-stratigraphic evolution; offshore Uruguay